INVENTORY MANAGEMENT IN DELTA ALLIED WIRE INDUSTRIES LIMITED ASABA (Nigerian Journal of Technology, 2008)
A good inventory system reduces production cost and consequently increases profit. Optimum management of inventory in the Delta – Allied Wire Industries Limited was studied in this research. The information needed was obtained through questionnaire and interviews of key staff of the company. Data collated were recorded for the operational 5 years period (1997 – 2001) under review and customers’ handling processes equally studied for improvement. The data collated were collated were analyzed using the Economic Order Quantity (EOQ) model under constant demand, non-instantaneous receipt as well as other possible scenarios. Results showed that if the order had been reduced from 12 per year to 2 or at most 5 per year savings of ?602, 876 to ?2,977,253 could have been made under constant demand. In addition, the company will have even greater saving if it encourages customers to purchase directly from the company than through the warehouses, thereby reducing the carrying cost. Recommendations based on the findings were made to the company for inclusion in future financial management planning and control.